Insomnia Disorders in Final-Semester College Students: A Case Study on Their Behavioral Patterns - Nurhalifah, Indah; Furbaningrum, Iin; Ummah, Nurul Wihdatul; Umam, Muhammad Fikri; Ramanda, Peni (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to explore the experiences, contributing factors, impacts, and coping strategies related to insomnia among final-year college students. The subjects of this research were two college students, identified by the initials HM and MD, who had experienced insomnia for more than one month. A qualitative case study method was employed, with in-depth interviews as the primary data collection tool. The findings indicate that both participants suffered from sleep disturbances triggered by academic pressure, excessive anxiety, frequent use of electronic devices before bedtime, and unhealthy lifestyle habits. The study concludes by emphasizing the importance of psychosocial support from educational institutions and the need to enhance college students’ awareness of stress management and healthy sleep patterns. The implications of this research serve as a basis for higher education institutions to design psychological support programs that are more responsive to the specific needs of final-year college students.